2009
DOI: 10.1094/mpmi-22-1-0096
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Type III Secretion Effectors in Xanthomonas oryzae pv. oryzae

Abstract: Many gram-negative bacteria secrete so-called effector proteins via a type III secretion (T3S) system. Through genome screening for genes encoding potential T3S effectors, 60 candidates were selected from rice pathogen Xanthomonas oryzae pv. oryzae MAFF311018 using these criteria: i) homologs of known T3S effectors in plant-pathogenic bacteria, ii) genes with expression regulated by hrp regulatory protein HrpX, or iii) proteins with N-terminal amino acid patterns associated with T3S substrates of Pseudomonas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 70 publications
2
77
0
2
Order By: Relevance
“…Nine non-TAL effectors have been identified in the Chinese strain 13751, among which XopR 13751 has been shown to affect virulence in Xoo [43]. In the present study, we chose XopN KXO85 to evaluate functional roles in the KXO85 strain and confirmed that it is secreted in an Hrp T3SS-dependent manner, translocated into the plant cytoplasm, and that its gene expression is regulated by HrpX KXO85 , as reported previously for other Xoo strains [13]. Among the Xop homologs in KXO85, we found that XopN KXO85 is the most critical for Xoo virulence in the Korean strain KXO85.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Nine non-TAL effectors have been identified in the Chinese strain 13751, among which XopR 13751 has been shown to affect virulence in Xoo [43]. In the present study, we chose XopN KXO85 to evaluate functional roles in the KXO85 strain and confirmed that it is secreted in an Hrp T3SS-dependent manner, translocated into the plant cytoplasm, and that its gene expression is regulated by HrpX KXO85 , as reported previously for other Xoo strains [13]. Among the Xop homologs in KXO85, we found that XopN KXO85 is the most critical for Xoo virulence in the Korean strain KXO85.…”
Section: Discussionsupporting
confidence: 73%
“…The T3SS of plant pathogenic species of Pseudomonas , Xanthomonas , Erwinia , and Ralstonia is highly conserved and involved in translocation of T3SS-dependent effector proteins from bacterial cells into plant cells [712]. These effector proteins are categorized into two groups: transcription activator-like (TAL) effectors and non-TAL effectors [11,1315]. In Xoo , T3SS that is essential for virulence is encoded by hypersensitive response and pathogenicity (hrp) genes, the expression of which is controlled by HrpX [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in Xanthomonas spp. demonstrated that HpaB is important for T3E secretion/translocation 27, 28, 47, 48 . In Xanthomonas axonopodis pv.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria growth in planta was measured as reported previously. 26) To analyze bacterial growth, inoculated rice leaves (length 1 cm) were collected at 5 dpi. Leaves were ground in and diluted with sterile water, then plated on a peptone-sucrose medium containing rifampicin and kanamycin to count bacterial numbers.…”
Section: Methodsmentioning
confidence: 99%